Artificial intelligence for the Internet of everything - Lawless, William; Mittu, Ranjeev; Sofge, Donald; Moskowitz, Ira S., 1956-; Russell, Stephen (Academic Press, an imprint of Elsevier, 2019)
Considering the foundations, metrics and applications of Internet of Everything (IoE) systems, this book covers whether devices and IoE systems should speak only to each other, to humans or to both. --